Kinetic Parameters of Thermolysis of Complexes of Rhodium(III), Palladium(II) and Platinum(II) with Substituted Morpholines from their Non-Isothermal Thermogravimetric Data - Agrawal , H.L.; Ambasta, R.K.; Verma, L.; Verma, R.K.; Verma, B.P.; Mishra, A. (Asian Journal of Chemistry, 2010)
The non-isothermal decomposition of complexes of Rh(III), Pd(II) and Pt(II) with N-substituted methyl and ethyl morpholines bas been studied in static air. The TG data have been analysed for the kinetic parameters of decomposition using the graphical Freeman-Carroll method and the trial and error method of Zsako.